Wellbeing: As a Mediator of the Influence of Spiritual Leadership on Employee Creativity - Dwi Widyani Anak Agung; I Nyoman Teja Sukma Dwijendra; Ni Kadek Ananda Putri Anggarani (Universitas Warmadewa, 2023)
This study aims to examine wellbeing as a mediator of the influence of spiritual leadership on the creativity of employees at Village Credit Institutions (LPD). The study was conducted on LPDs in Tabanan district which had the highest number of healthy LPDs. Determination of the number of research samples obtained by a number of 75 LPD employees, using the slovin formula with a precision of 10 percent. Respondents were determined by simple random sampling from a number of LPDs in Tabanan district. Analysis of research data using smartPLS 3.2.9. The results of this study indicate that spiritual leadership and wellbeing have a significant positive effect on the creativity of LPD employees, spiritual leadership has a significant positive effect on wellbeing, and wellbeing plays a role as a mediating influence of spiritual leadership on the creativity of LPD employees.